2018
DOI: 10.1371/journal.pone.0193794
|View full text |Cite|
|
Sign up to set email alerts
|

Bold personality makes domestic dogs entering a shelter less vulnerable to diseases

Abstract: It is widely recognised that for vertebrate species, personalities vary along an axis with extremes represented by ‘proactive’ and ‘reactive‘ individuals. The aim of this study was to verify whether there is a relationship between personality and disease vulnerability in domestic dogs (Canis familiaris) exposed to an intensely stressful situation such as entering a shelter. Twenty-eight shelter dogs participated in the study. The ethogram consisted of approximately 100 behavioural patterns. Behavioural observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…We measured higher ROM levels in zymosan-treated bats, but these levels were already higher right from the first sampling and did not show further increases during the following days, which renders interpretation difficult. It might be that the concentration of ROMs is linked to haptoglobin and haptoglobin inhibited the increases due to its anti-oxidant effect (Sauerwein et al, 2005; van de Crommenacker et al, 2010; Corsetti et al, 2018). It is therefore conceivable that an increase in ROMs took place during the first arousal early in the experiment as a response against the antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured higher ROM levels in zymosan-treated bats, but these levels were already higher right from the first sampling and did not show further increases during the following days, which renders interpretation difficult. It might be that the concentration of ROMs is linked to haptoglobin and haptoglobin inhibited the increases due to its anti-oxidant effect (Sauerwein et al, 2005; van de Crommenacker et al, 2010; Corsetti et al, 2018). It is therefore conceivable that an increase in ROMs took place during the first arousal early in the experiment as a response against the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…P -values were adjusted for multiple comparisons by using Tukey's method in the ‘emmeans’ package (Lenth et al, 2019). Because haptoglobin may correlate with ROM (Corsetti et al, 2018; Sauerwein et al, 2005; van de Crommenacker et al, 2010), the relationship was calculated by using the Pearson's rank correlation for each treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…However, they found that dogs displaying the proactive style (higher boldness, higher sociability) had a lower incidence of illness; our current results seem to be contrary to this previous data. However, Corsetti et al[26] did not find any statistically significant predictors when assessing individual traits, such as boldness, activity, sociability, or anxiety; the lack of statistically significant correlations among individual traits to illness may have been due to a relatively small sample size. Additional research may be needed to reconcile these contrary findings.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Svartberg and Forkman[36] suggested that various traits, such as sociability and exploration, among others, may be related to a single higher-order dimension. Corsetti and colleagues[26] have also combined the individual traits of activity, attentiveness, dominance, and sociability to differentiate dogs into proactive and reactive coping styles. However, they found that dogs displaying the proactive style (higher boldness, higher sociability) had a lower incidence of illness; our current results seem to be contrary to this previous data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation